PERANAN BIMBINGAN DAN KONSELING DALAM MENGATASI MASALAH BELAJAR SISWA - Siregar, Risdawati (FORUM PAEDAGOGIK, 2014)
AbstractLearning problem is an abstacle or abstacles faced by individuals in order to actieve the expected goals of lerning activities for each individuals, ar not always abte to take place fairly, sometimes smoothly, sometimes fast catching lessons. So the only people having problems learning such as : low lerning actievement, not a concentration in learning, there is now motivation to learn, poorhabits in learning and others.So to resolve the issue needs to handle the role of guidance counseling so that participants can follow the activities learn well and achieve optimal learning outcomes and develop a personality that leads to the formation of mature and independent attitude.In counseling there are several types of services provided by a guidance counselor to help students who have trouble learning the basic services that are psikisimprove skill and good study habits, motivate and increase the faith and devotion to Allah and aware of the obligation, either to him self and the environment in accordance with the rules of Islamic teachings.Key word : Islamic guidance counseling , learning problem.